Oral Microcapsule Chromocolonoscopy With Patent Blue V Improves Adenoma Detection Safely and Effectively - Schulte, Berenice; Waetzig, Georg H.; Bethge, Johannes; Aden, Konrad; Conrad, Claudio C.; Theismann, Eva‐Maria; Keppler, Julia K.; Ruhmlieb, Therese; Schwarz, Karin; Schreiber, Stefan; Ellrichmann, Mark (United European gastroenterology journal, 2025)
Chromocolonoscopy significantly improves polyp/adenoma detection rates (PDR/ADR). However, its integration into routine clinical practice is hindered by its cumbersome mode of application. The objective was to develop an oral nutritional grade delivery system and to assess its efficacy for colonic release, mucosal staining and PDR/ADR as a proof of concept. Food-grade shellac microcapsules releasing 87.5 mg of patent blue V (PBM) pH- and time-dependently were used in 35 volunteers receiving diagnostic colonoscopy either due to a positive fecal occult blood test or surveillance in inflammatory bowel disease. Six capsules were administered p.o. during the bowel preparation (Klean-Prep). Mucosal staining was assessed in total and per segment using a five-point grading scale. PDR and ADR were evaluated and compared to a propensity score-matched comparison cohort in a 1:3 ratio. In the PBM cohort, 97.1% (34/35) achieved an optimal to acceptable staining quality (SQ) score of ≥ 8, with a mean total score of 13.4 ± 2.9. PDR was significantly higher in the PBM group at 62.8% compared to 42.9% in the comparison group (CG; p = 0.04). ADR showed no significant differences (p = 0.06). The use of PBM resulted in a significantly increased number of detected polyps and adenomas per colonoscopy compared with CG (polyps: PMB = 1.1 ± 1.1 vs. CG = 0.6 ± 0.8, p = 0.02; adenomas: PBM = 0.8 ± 0.9 vs. CG = 0.3 ± 0.5; p = 0.02). The novel PBM demonstrated uniform mucosal staining when utilized in chromocolonoscopy. Delayed-release patent blue V appears to be a safe and effective alternative to dye-spray techniques and existing oral chromoendoscopy modalities.